2021
DOI: 10.1002/advs.202003937
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polymeric Nanoparticles for Blood–Brain Barrier Transfer—Strategies and Challenges

Abstract: Neurological disorders such as Alzheimer's disease, stroke, and brain cancers are difficult to treat with current drugs as their delivery efficacy to the brain is severely hampered by the presence of the blood-brain barrier (BBB). Drug delivery systems have been extensively explored in recent decades aiming to circumvent this barrier. In particular, polymeric nanoparticles have shown enormous potentials owing to their unique properties, such as high tunability, ease of synthesis, and control over drug release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(177 citation statements)
references
References 354 publications
0
154
0
Order By: Relevance
“…Animal model results showed that drug uptake in the brain increased four-fold for PBCA NPs coated with 1% PS 80 compared to free drugs. Several studies have demonstrated that PS 80-coated NPs can improve drug accumulation in the brain [124][125][126][127][128][129][130][131]. It has been reported that brain targeting of PS 80-coated NPs is closely associated with the interaction between PS 80 coating and brain microvessel endothelial cells [132].…”
Section: Ps-coated Nps For Efficient Bbb Transportmentioning
confidence: 99%
“…Animal model results showed that drug uptake in the brain increased four-fold for PBCA NPs coated with 1% PS 80 compared to free drugs. Several studies have demonstrated that PS 80-coated NPs can improve drug accumulation in the brain [124][125][126][127][128][129][130][131]. It has been reported that brain targeting of PS 80-coated NPs is closely associated with the interaction between PS 80 coating and brain microvessel endothelial cells [132].…”
Section: Ps-coated Nps For Efficient Bbb Transportmentioning
confidence: 99%
“…Therefore, in vitro models that better recapitulate the physiology, variability and complexity of cellular barriers are under rapid development and may be exploited to study inflammation, disease mechanisms and progression [15][16][17][18][19][20][21][22][23][24]. These models possess enormous potential in advancing drug development and discovery by developing techniques and approaches that could facilitate the delivery of therapeutic drug candidates across these barriers [25,26] to reach their target tissue and successfully treat diseases of organs protected by these barriers.…”
Section: Introductionmentioning
confidence: 99%
“…These protein complexes are mainly comprised of occludin, claudin, and junctional adhesion molecules. These three specialised proteins interact to develop an intricate, tight barrier that is exclusive to the cerebro-endothelial cells [ 31 ]. The apical part of the endothelial cell is exposed to the brain’s blood capillaries, and the basolateral part is exposed to the cerebrospinal fluid supported by the basement membrane.…”
Section: The Blood–brain Barrier (Bbb)mentioning
confidence: 99%